2022
DOI: 10.3390/biomedicines10030637
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Pan-Cancer Analysis of Kinesin Family Member C1 (KIFC1) in Human Tumors

Abstract: Kinesin family member C1 (KIFC1) is a minus-end-directed motor protein that is critically involved in microtubule crosslinking and spindle formation. KIFC1 is essential for supernumerary centrosomes, and it is associated with the initiation and progression of cancers. In the present study, we initially reviewed the The Cancer Genome Atlas database and observed that KIFC1 is abundantly expressed in most types of tumors. We then analyzed the gene alteration profiles, protein expressions, prognoses, and immune re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 65 publications
2
7
0
Order By: Relevance
“…In the present study, we firstly indicated the tumor‐promoting effects of KIFC1 in PC even in PC cells with DDX6 knockdown, suggesting that the carcinogenesis mediated by DDX6 was achieved probably by upregulation of KIFC1 expression. Wu et al 28 demonstrated that targeting the cell cycle and cell division may be the main mechanisms for the effect of KIFC1 on carcinogenesis. The positive effects of KIFC1 on the cell cycle were also observed in PC cells, and cell proliferation was increased by KIFC1 overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we firstly indicated the tumor‐promoting effects of KIFC1 in PC even in PC cells with DDX6 knockdown, suggesting that the carcinogenesis mediated by DDX6 was achieved probably by upregulation of KIFC1 expression. Wu et al 28 demonstrated that targeting the cell cycle and cell division may be the main mechanisms for the effect of KIFC1 on carcinogenesis. The positive effects of KIFC1 on the cell cycle were also observed in PC cells, and cell proliferation was increased by KIFC1 overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…An integrative pan-cancer study by Wu et al . found that KIFC1 was rarely perturbed at the genetic level in LUAD and other tumor types, suggesting genetic mechanisms are unlikely to account for KIFC1 overexpression[34]. Further studies are needed to decipher the mechanisms driving KIFC1 overexpression but ample evidence indicates that KIFC1 expression is a robust prognostic biomarker in LC.…”
Section: Discussionmentioning
confidence: 99%
“…The recurrence of CA and KIFC1 overexpression in lung tumors, and the dependence of LC with CA on KIFC1 emphasize its therapeutic potential[33, 34]. We propose that KIFC1-targeted therapy could provide a novel strategy for potentiating GIN to lethal levels by forcing LC to divide with multipolar spindles, and that CA and KIFC1 expression could serve as biomarkers to guide effective use.…”
Section: Discussionmentioning
confidence: 99%
“…We also detected the overexpression of PCLAF, a factor associated with PCNA (also overexpressed in AML), that is associated with DNA synthesis and the G1/S transition (26). On the other hand, we detected several underexpressed genes involved in the regulation of the mitotic spindle and chromosome segregation, namely KIFC1, CENPF, CENPI, ASPM (27)(28)(29)(30)(31)(32). This suggests that the leukemic cells are actively proliferating, but the mechanisms related with the quality of cell division are downregulated, which could trigger genomic irregularities, like aneuploidies, which are a hallmark of cancer.…”
Section: R a F Tmentioning
confidence: 90%